Comparison Of Chloral Hydrate Solution, Hydroxyzine Syrup And Lidocaine/Prilocaine Cream As Premedication For Lumbar Puncture In Children, A Double Blind Study - esfahani, Hossein; Sedighi, Iraj; Sahraei Ardakani, Maryam; Seif Rabie, Mohammad Ali; hosseini, firozeh (Iranian Journal of Child Neurology, 2022)
Objectives This study aimed to compare the clinical effectiveness of oral hydroxyzine and chloral hydrate to topical lidocaine/prilocaine 2.5% cream as premedication in pediatric leukemia patients. Material & Methods This double-blind clinical trial study was conducted on 70 leukemic and non-leukemic patients aged 3-11 years old. The patients were divided into 4 groups as follow: in the group A, choral hydrate solution was given in 18 patients, in group B hydroxyzine syrup was used in the same number of patients, in group C, chloral hydrate solution and Lidocaine/Prilocaine cream were used in 17 patients, and in group D hydroxyzine syrup and Lidocaine/Prilocaine cream were given in the same number of patients. These groups were assessed and judged based on visual analog scale (VAS). Side effects of the drugs were also recorded. Results In this study, 54.3% (38) of cases were girls and 45.7% (32) were boys. Patients’ selection was included as follow: ALL in 77%, AML in 7.2% and non-leukemic cases in 15.8% of cases. The VAS test showed no difference in these four groups. Non-Traumatic lumbar puncture (RBC<50) were seen in 97.1% of cases. Conclusion Although the use of pre-medications for lumbar puncture with hydroxyzine syrup and chloral hydrate solution was not statistically effective, it did lead to increased patient and parent satisfaction. Also, adding the Lidocaine/Prilocane cream does not improve the effectiveness of the drugs.